Mechanical properties of dissimilar aluminum-based alloy joints by mig welding - Ahmad Danial, Abdullah (2012)
This thesis deals with the investigation of microstructure and mechanical properties of weld joint of AA5052-H32 and AA6061-T6 aluminum alloys by using MIG welding process. The objective of this thesis is to investigate the effect of parameters to the mechanical properties and microstructure of AA5052-H32 and AA6061-T6. The thesis describes the proper MIG welding process using automatic table in order to investigate the effect on microstructure and mechanical properties of weld joint of AA5052-H32 and AA6061-T6. The aluminum ER5356 was used as filler in this experiment. The studies of mechanical properties that are involved in this thesis consist of toughness, tensile strength of AA5052-H32 and AA6061-T6 weld joint before and after MIG welding process. Four different parameters were used in order to determine the correlation between mechanical properties and microstructure of the weld joint. As a result, it is observed that the current is the parameter which has the highest influence to the UTS and toughness and it is followed by torch angle, speed and lastly weld passes. The optimum parameter for the highest value of UTS and toughness is found; current=90A, torch angle=+15, speed=4mm/s and weld pass=1. The microstructure shows crack sensitivity and porosity which decreases the strength and toughness of weld joint. As for the recommendation, the other properties including hardness, corrosion resistance should be considered in order to optimally select a material for its specific application.